Analysis of mutations of PARP1, RNF213, PAX8, KMT2C, MTRR in malignant mesothelioma of testicular tunica vaginalis testis - Kowalik, Artur; Wincewicz, Andrzej; Zięba, Sebastian; Baran, Wojciech; Kopczyński, Janusz; Koda, Mariusz; Sulkowski, Stanisław; Goźdź, Stanisław (Polish Journal of Pathology, 2020)
Molecular next gene sequencing was used to evaluate mutations in 409 common mutated cancer-related genes in malignant mesothelioma of tunica vaginalis testis (MMTVT) of 81-year-old man. Multifocal papillary-solid areas contained necrosis among highly cellular fields with multiple mitoses. It was positive for WT1, CKAE1/AE3, calretinin, CK7 with negativity for CK5, PSA, TTF-1. Following mutations were revealed in PARP1 (NM_001618: c.2285T<C p.V762A), RNF213 (NM_001256071: c.3121G G, p.K135R), MTRR (NM_024010: c.147A>G, p.I49M) and two sorts of mutations in structure of KMT2C gene (NM_170606: c.2447_2448insA (c.2447dupA), p.Y816fs and NM_170606: c.1042G>A, p.D348N) for the first time in MMTVT.